Molecular phylogenetics of Neotropical detritivorous fishes of the family Curimatidae (Teleostei: Characiformes) - Melo, Bruno [UNESP]; Sidlauskas, Brian; Hoekzema, Kendra; Vari, Richard; Dillman, Casey; Oliveira, Claudio [UNESP] (Elsevier B.V., 2018)
Curimatidae, the fourth largest family of detritivorous Neotropical characiform fishes, encompasses eight extant genera and over 110 species dwelling in diverse freshwater habitats from Costa Rica to Argentina. Extensive phylogenetic analyses of soft anatomy and osteology provided evidence for intergeneric and most interspecific relationships, and formed the basis of curimatid taxonomy for nearly 40 years. However, that morphological phylogeny demonstrated incomplete phylogenetic resolution at various scales and has never been tested with extensive molecular data. Herein, we infer molecular phylogenies spanning similar to 70% of the known species diversity using three nuclear and three mitochondrial loci. Topologies from concatenated likelihood and Bayesian analyses and coalescent Bayesian species trees agree broadly with each other, and with the prior morphological hypothesis in many, but not all respects. All molecular analyses support the monophyly of Curimatidae and of six of its constituent genera, and agree on the placement of Curimatopsis as sister to all other curimatids. DNA-based intergeneric relationships differ substantially from prior morphological hypotheses by placing Curimata sister to Potamorhina and Psectrogaster sister to Pseudocurimata, rather than in a ladderized arrangement. Our results also resolve a major uncertainty in the morphological tree by revealing Cyphocharax, a genus for which no anatomical synapomorphy has ever been proposed, as a paraphyletic assemblage containing a monophyletic Steindachnerina and a polyphyletic Curimatella. Overall, the phylogeny expands substantially our understanding of the morphology, phylogenetics and evolution of the Curimatidae, and will guide future intrageneric studies by improving precision in the choice of comparative taxa.
Keywords: Freshwater fishes; Morphological evolution; Multilocus analysis; Systematics; *BEAST